Bone morphology of the hind limbs in two caviomorph rodents - De Araújo, F. A P [UNESP]; Sesoko, N. F. [UNESP]; Rahal, Sheila Canevese [UNESP]; Teixeira, Carlos Roberto [UNESP]; Müller, T. R. [UNESP]; Machado, M. R F [UNESP] (Wiley, 2013)
In order to evaluate the hind limbs of caviomorph rodents a descriptive analysis of the Cuniculus paca (Linnaeus, 1766) and Hydrochoerus hydrochaeris (Linnaeus, 1766) was performed using anatomical specimens, radiography, computed tomography (CT) and full-coloured prototype models to generate bone anatomy data. The appendicular skeleton of the two largest rodents of Neotropical America was compared with the previously reported anatomical features of Rattus norvegicus (Berkenhout, 1769) and domestic Cavia porcellus (Linnaeus, 1758). The structures were analyzed macroscopically and particular findings of each species reported. Features including the presence of articular fibular projection and lunulae were observed in the stifle joint of all rodents. Imaging aided in anatomical description and, specifically in the identification of bone structures in Cuniculus paca and Hydrochoerus hydrochaeris. The imaging findings were correlated with the anatomical structures observed. The data may be used in future studies comparing these animals to other rodents and mammalian species. © 2012 Blackwell Verlag GmbH.
Keywords: Agouti paca; Animalia; Cavia; Cavia porcellus; Caviomorpha; Hydrochaeris hydrochaeris; Mammalia; Rattus; Rattus norvegicus; Rodentia